Rational design of bi-functional RE3+ (RE = Tb, Ce) and alkali metals (M+ = Li, Na, K) co-doped CaAl2O4 nanophosphors for solid state lighting and advanced forensic applications. (July 2019) - Shashikala, B.S.; Premkumar, H.B.; Darshan, G.P.; Nagabhushana, H.; Sharma, S.C.; Prashantha, S.C.
Graphical abstract: Highlights: The RE 3+ and alkali metal ions co-doped CaAl2 O4 nanophosphors were synthesized by bio-inspired solution combustion route. With co-doping, the 2-fold enhancement in the PLE intensity was noticed. The photometric properties confirm intense green emission with high color purity. Well defined LFPs ridge characteristics with high sensitivity, without hindrance and selectivity are revealed. Abstract: Novel CaAl2 O4 :Tb 3+, Ce 3+, M + (M + = K, Na, Li) nanophosphor was fabricated by bio-inspired solution combustion route by using lemon juice as a fuel. PXRD profiles endorse monoclinic phase in all samples irrespective of the dopants. The photoluminescence emission spectra exhibit peaks in the range at ˜450–650 nm, which were attributed to 5 D4 → 7 FJ (J = 6, 5, 4 and 3) transitions of Tb 3+ ions. With increases of concentration of co-dopant Ce 3+ ions, the rate of energy transfers from Ce 3+ to Tb 3+ ions also increase, which may lead to enhanced emission. Moreover, the two-fold enhancement of the PLE intensity was noticed in M + co-doped CaAl2 O4 : Tb 3+, Ce 3+ nanophosphor. The high purity green color emission was confirmed from photometric characterization. The visualized LFPs using optimized sample exhibit high sensitivity, selectivity without background hindrance. Aforementioned results confirm that the prepared nanophosphor might be a classical material for WLEDs and advanced forensic applications.